1975
DOI: 10.1002/1520-6807(197507)12:3<334::aid-pits2310120318>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control: A proposal for change

Abstract: 1':nvit o~rmental control as expressed in the internal-external locus of control construct continues l o remain unchallenged as a major association variablc in academic achievement. Research studies are cited that suggest that internality may well be preferred to externality if one values power over one'h destiny. The writer proposes a peer-teaching-peer strategy that utilizes the low-achieving External as the tutor, a reversal of the usual procedure. The ,assumption is that the External must experience and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In earlier research with the more general Internal-External Locus of Control Scale (/-E; Rotter, 1966) it had been found that internals were more observant and socially perceptive during social interactions than were externals (Lefcourt & Wine, 1969). Similarly, Chandler (1975) noted that among children, internals experienced less difficulty in interaction with their peers and teachers in classrooms and playgrounds than did externals.…”
mentioning
confidence: 99%
“…In earlier research with the more general Internal-External Locus of Control Scale (/-E; Rotter, 1966) it had been found that internals were more observant and socially perceptive during social interactions than were externals (Lefcourt & Wine, 1969). Similarly, Chandler (1975) noted that among children, internals experienced less difficulty in interaction with their peers and teachers in classrooms and playgrounds than did externals.…”
mentioning
confidence: 99%
“…Pugh (1993) further argued that the longer one is incarcerated, the more external he is likely to become in locus of control. Investigators have argued that external locus of control can be moved to the direction of internality through intervention (Chandler, 1975;Pugh, 1993). Indeed, Williams, Omizo, and Abrams (1984) found that parents who completed a parenting course perceived their own behavior as more of a causative factor in their children's behavior.…”
Section: The Present Investigationmentioning
confidence: 99%
“…The use of positive, selfassuring adult-evaluation also appears to promote a sense of internal control while peer-evaluation inhibits the growth of internal expectancies for control. Chandler (1975) discussed the usefulness of tutoring as a means of enhancing internal locus of control. He presented data which showed under-achieving junior-highschool students who tutored under-achieving second-and third-grade charges, increased in internal control (Bialer scale) after their tutoring experience.…”
Section: Modification Of Locus Ofmentioning
confidence: 99%